ANALISIS SISTEM REKRUTMEN TENAGA KERJA PADA CV. MITRA SEJATI DI SAMARINDA - Aljazair, Andy (EKONOMIA, 2013)
ABSTRACTANDY, Manpower Recruitment System Analysis at CV. Mitra Sejati in Samarinda. Under the guidance of Mr. and Mrs. Eddy Soegiarto K and Eka Yudhyani.       This study aims to determine the recruitment system at CV. Mitra Sejati in Samarinda.            Problem formulation in this study is: "Is Labour Recruitment System on CV. Mitra Sejati in Samarinda is in conformity with the standard ". The hypothesis in this study is: "Suspected Manpower Recruitment System by CV. Mitra Sejati in Samarinda not in accordance with the Standard "           Management is a science that studies the art of control / work done through other people, through the maintenance of SDM, Planning, Coordination, and guidance in achieving goals leads organisasi.And SDM Management One study of the utilization of human resources to gain an effective and efficient in achieving organizational goals.           Analysis and hypothesis testing tools used by Descriptive Analysis / arguments - arguments and reasons underlying the procedures used in the Workforce Recruitment CV. Mitra Sejati in Samarinda.           Results of the analysis showed that the recruitment system in the CV. Mitra Sejati are not in accordance with the standards of recruitment on the generally. because its workforce in priority is just not the right Human Resources - fully competent, so menyebapkan rights - the right of workers not being met. From the analysis and findings - findings that in the mentioned field data shows that the hypothesis is accepted. because although the same - the goal is the same but the recruiting of analysis is evident from all of the criteria set percentage of that 62% recruitment system is not the same, the same, while only 38%. Of all the criteria set out, for the system of recruitment between CV. Mitra Sejati and Richard Nata is not the same.          With the early stages of determining the amount of  labor required, for labor, selecting applicants archives, testing candidates, interviewing candidates and decide duterima labor and make labor agreements with employees or prospective employment contract (written agreement). Stages - the stages that have been described will produce competent human resources and qualified according to the criteria of the company.